2007
DOI: 10.2337/dc06-1551
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Telmisartan Versus Ramipril on Renal Endothelial Function in Patients With Hypertension and Type 2 Diabetes

Abstract: OBJECTIVE -One of the earliest signs of vascular change is endothelial dysfunction, which is also known to provoke albuminuria and to predict cardiovascular prognosis. The aim of this study was to analyze the effects of renin-angiotensin system (RAS) blockade on renal endothelial function.RESEARCH DESIGN AND METHODS -In a multicenter, prospective, double-blind, forced-titration, randomized study, 96 patients with type 2 diabetes, hypertension, glomerular filtration rate Ͼ80 ml/min, and normo-or microalbuminuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
1
16

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 45 publications
4
76
1
16
Order By: Relevance
“…Only quinapril induced net change in the acetylcholineprovoked constriction of target segments of the coronaries after 6 months of treatment in a population formed of normotensive patients with coronary artery disease and without confounding variables such as heart failure, cardiomyopathy, or major lipid abnormalities. Similar results of improvement of flow-dependent endothelium-mediated vasodilation are reported in further two studies: the first, even in subjects affected by CAD, reported a similar extent of reduction after 4 weeks of therapy with ramipril 10 mg/d or losartan 100 mg/d through increase of bioavailability of NO [220]; the second, evaluated in renal circulation, after once daily treatment with 40/80 mg telmisartan or 5/10 mg ramipril for 9 weeks [221]. No significant differences between the two drugs were observed although the ARB seemed to be a little more efficient.…”
Section: Part IV -Anti-inflammatory Effects Of Ace-isupporting
confidence: 68%
“…Only quinapril induced net change in the acetylcholineprovoked constriction of target segments of the coronaries after 6 months of treatment in a population formed of normotensive patients with coronary artery disease and without confounding variables such as heart failure, cardiomyopathy, or major lipid abnormalities. Similar results of improvement of flow-dependent endothelium-mediated vasodilation are reported in further two studies: the first, even in subjects affected by CAD, reported a similar extent of reduction after 4 weeks of therapy with ramipril 10 mg/d or losartan 100 mg/d through increase of bioavailability of NO [220]; the second, evaluated in renal circulation, after once daily treatment with 40/80 mg telmisartan or 5/10 mg ramipril for 9 weeks [221]. No significant differences between the two drugs were observed although the ARB seemed to be a little more efficient.…”
Section: Part IV -Anti-inflammatory Effects Of Ace-isupporting
confidence: 68%
“…При этом только телмисартан достоверно снижал сосудистое сопротивление в почках, улучшал почечный кровоток в покое и достоверно повышал уровень ади-понектина -цитокина, выделяемого адипоцитами, улучшающего углеводный обмен [29].…”
Section: Angiotensin Receptor Blockers With Pleiotropic Properties блunclassified
“…Противовоспалительные эффекты PPAR-g за-ключаются в снижении выработки фактора роста фиб-робластов, молекул клеточной адгезии, воспалитель-ных цитокинов [31]. Активация PPAR-g улучшает функ-цию эндотелия [32], в том числе, у пациентов с СД и по-ражением почек [29]. Механизм действия широко…”
Section: Angiotensin Receptor Blockers With Pleiotropic Properties блunclassified
“…16 The recently published Telmisartan versus Ramipril in renal Endothelial DYsfunction (TRENDY) study provided the fi rst head-to-head comparison of an ARB and an ACE inhibitor on renal endothelial function. 30 TRENDY was performed in 96 patients with type 2 diabetes who had mild-to-moderate hypertension (seated SBP/diastolic blood pressure [DBP] 140 to 180/90 to 110 mm Hg), normo-or microalbuminuria, and GFR Ͼ 80 mL/minute/1.73 m 2 . Patients were randomized to either telmisartan 40 mg or ramipril 5 mg for 3 weeks, followed by telmisartan 80 mg or ramipril 10 mg for 6 weeks.…”
Section: Role Of Drugs Blocking Raasmentioning
confidence: 99%